Gangs, violence, and fear: punitive Darwinism in El Salvador - Rosen, Jonathan D. (Crime, law and social change, 2023)
This article evaluates the factors impacting support for tough on crime policies in El Salvador. Examining theoretical and empirical scholarly work, we look at how fear, together with social and political contexts drive public appetite for punitive policies towards criminals. We show that President Nayib Bukele is responding to public opinion and has implemented tough on crime policies at the expense of human rights violations and democratic institutions. Society favors candidates who are the "toughest" against criminal actors. Political candidates from all sides of the ideological spectrum tap into the fear of the populace to win votes, leading to punitive Darwinism. We provide an empirical assessment of which theoretically relevant factors are statistically associated with punitivism in the Salvadoran context, using multiple regression analysis of high-quality public opinion survey data from LAPOP.